PENGGUNAAN AIR REBUSAN KACANG MERAH SEBAGAI SUBSTITUSI PUTIH TELUR (AQUAFABA) DALAM PEMBUATAN FRENCH MERINGUE: PENDEKATAN ORGANOLEPTIK - Selvi Novianti (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This research will contribute to the development of the latest basic produtct of egg white substitute whic is aquafaba. The objective of this research is to find out that aquafaba not only can be produced from canned chickpeas but also from another variant of beans which is kidney bean and can be made into French meringue as one of pastry basic product. Furthermore, the methodology of this research is experimental of which researcher undergone two treatments and chose reduced red kidney stewed water as it formed a satisfactory French meringue. This research used descriptive analysis to analyze the observation and interview results from expert panelists in the aspects of sensory aproach. Moreover, results shown that red kidney stewed water can be used to make aquafaba and can produced a satisfactory French meringue in terms of appearance, flavor and texture.